PREVENTION OF CERVICAL CANCER - Patiyus Agustiansyah (Conferences of Medical Sciences Dies Natalis, 2021)
Cervical cancer is the fourth most common cancer in women globally. In 2018, 570.000 women were diagnosed with cervical cancer, and 311.000 of them died from the disease.1 In Indonesia, cervical cancer is the second most common cancer. According to GLOBOCAN, there was a decrease in incidence from 17.2% to 9.2% from 2018 to 2020. This decrease has also been seen in other countries such as the United States. However, the distribution of cervical cancer varies widely among countries. WHO projected that the global burden of cervical cancer is projected to continue to increase, rising to 700 000 cases (21% increase) and 400 000 deaths (27% increase) in 2030 compared to 2018. Preventive measures become an important step to manage this situation. Preventions such as HPV vaccination, screening, and treatment of precancerous lesions have been found to be effective.